Flexible Morphogenesis based Formation Control for Multi-Robot Systems - Jan Carlo Barca; Eugene Eu-Juin Lee; Ahmet Sekercioglu (IAES International Journal of Robotics and Automation (IJRA), 2013)
Inspired by how biological cells communicate with each other at a cell-to-cell level; morphogenesis emerged to be an effective way for local communication between homogenous robots in multi-robot systems. In this paper, we present the first steps towards a scalable morphogenesis style formation control technique, which address the drawbacks associated with current morphogenesis type formation control techniques, including their inability to distribute robots evenly across target shapes. A series of experiments, which demonstrate that the proposed technique enables groups of non-holonomic ground moving robots to generate formations in less than 9 seconds with three robots and less than 22 seconds with five robots, is also presented. These experiments furthermore reveal that the proposed technique enables groups of robots to generate formations without significantly increasing the total travel distance when faced with obstacles. This work is an important contribution to multi-robot control theory as history has shown that the success of groups often depends on efficient and robust formation control.